2013
DOI: 10.1111/imr.12143
|View full text |Cite
|
Sign up to set email alerts
|

Engineering T cells for cancer: our synthetic future

Abstract: Video podcast available Go to http://www.immunologicalreviews.com to watch an interview with Guest Editor Dr Carl June.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 77 publications
0
43
0
Order By: Relevance
“…Administration of T cells genetically modified to express Chimeric Antigen Receptor (CAR) is a novel approach with proven success in early phase human trials [1,2]. CARs consist of an antibody derived recognition domain, linked to signalling molecules that activate T cells upon interaction with cells expressing the respective target antigen on their surface [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Administration of T cells genetically modified to express Chimeric Antigen Receptor (CAR) is a novel approach with proven success in early phase human trials [1,2]. CARs consist of an antibody derived recognition domain, linked to signalling molecules that activate T cells upon interaction with cells expressing the respective target antigen on their surface [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…CARs consist of an antibody derived recognition domain, linked to signalling molecules that activate T cells upon interaction with cells expressing the respective target antigen on their surface [1,2]. A patient's own CARmodified T cells are amplified ex vivo to numbers suitable for adoptive cell therapy and administered to the patient after preconditioning.…”
Section: Introductionmentioning
confidence: 99%
“…The evolution of CARs was facilitated by multiple studies that revealed the molecular pathways and the dynamic features of TCR activation as well as the incorporation of these results into the design and composition of the synthetic CARs. 25 Progress in CAR design was accompanied by intensive development of animal models that could be used in preclinical studies to evaluate and improve the antitumor potency of CAR T cells. Typical in vivo models used immunodeficient mice into which human tumor xenografts or cell lines were transplanted at different locations (e.g., intraperitoneally, subcutaneously, and orthotopically) to mimic human tumors.…”
Section: Tumor-specific T-bodies For Cancer Treatmentmentioning
confidence: 99%
“…(Papadopoulos et al 1994, Rooney et al 1995) Initial studies focused on expanding T cells that recognized tumour antigens through their native receptors, but over the last decade there has been increasing interest in strategies to genetically modify T cells with T-cell receptors (TCRs) or chimeric antigen receptors (CARs) to confer new specificities. (Rooney et al 2014, Sadelain 2015, Vonderheide and June 2014) Indeed, this is an exciting time in the field of T-cell immunotherapy with in vitro discoveries paving the way for bench-to-bedside translation and resulting in remarkable clinical responses in a variety of haematological malignancies. In particular, adoptively transferred T-cells genetically modified to express CD19 CARs have shown great promise (Davila et al 2014, Lee et al 2015, Maude et al 2014), although some haematological malignancies remain recalcitrant.…”
Section: Introductionmentioning
confidence: 99%